2023
DOI: 10.1111/jcpp.13869
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐sequences of anger and shame and non‐suicidal self‐injury in youth: an ecological momentary assessment study

Abstract: ObjectiveNon‐suicidal self‐injury (NSSI) is a significant mental health concern with the highest prevalence among adolescents. NSSI has been conceptualized as one of the maladaptive strategies to cope with challenging affect or a form of self‐punishment. Although characterizing moment‐to‐moment associations between shame and NSSI in individuals' real‐world environment and partitioning between‐ and within‐person effects is critical for mobile and timely interventions, most studies examined habitual experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Self-criticism, like a generally negative self-view, is a well-known risk factor for engagement in NSSI (Zelkowitz & Cole, 2019), but it is possible that self-directed anger is a key component in determining who will engage in more severe NSSI. Anger is generally considered to be an "activating" emotion that increases the tendency to approach or engage in behaviors (Carver & Harmon-Jones, 2009), and previous research has demonstrated the importance of anger generally in NSSI (Cassiello-Robbins et al, 2021), as well as the importance of self-directed anger in NSSI (Dillon et al, 2021;Kudinova et al, 2024;Muehlenkamp et al, 2013). However, to our knowledge, no one has yet examined the relationships between self-directed anger, self-punishment motives, and NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Self-criticism, like a generally negative self-view, is a well-known risk factor for engagement in NSSI (Zelkowitz & Cole, 2019), but it is possible that self-directed anger is a key component in determining who will engage in more severe NSSI. Anger is generally considered to be an "activating" emotion that increases the tendency to approach or engage in behaviors (Carver & Harmon-Jones, 2009), and previous research has demonstrated the importance of anger generally in NSSI (Cassiello-Robbins et al, 2021), as well as the importance of self-directed anger in NSSI (Dillon et al, 2021;Kudinova et al, 2024;Muehlenkamp et al, 2013). However, to our knowledge, no one has yet examined the relationships between self-directed anger, self-punishment motives, and NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when subjected to verbal, physical, and social-relational aggression, adolescents may develop a negative self-appraisal of themselves as rejected and isolated, which lowers their self-esteem levels. Besides, concepts associated with low self-esteem, such as self-critical, 88 feelings of shame, 89 and self-punishment, 90 have been indicated as motivations for NSSI. These findings also demonstrated individuals with low self-esteem were more inclined to develop NSSI behavior, consistent with previous findings that the level of self-esteem was negatively correlated with the frequency and severity of NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, interpersonal life stress (e.g., arguments) often precedes or co-occurs with NSSI (35)(36)(37)(38). Interpersonal emotional processes, such as rejection sensitivity (39) and anger towards others (e.g., 40), are linked to NSSI behaviour over brief periods. NSSI may reduce negative affect, including interpersonally relevant emotions (e.g., guilt), shortly after engagement (e.g., 41-43; c.f.…”
Section: Introductionmentioning
confidence: 99%